ANALISIS KEMAMPUAN PENALARAN MATEMATIS DAN KONSEP DIRI SISWA SMP DITINJAU DARI GENDER - Oktavia, Serly; Zainudin, M (IKIP PGRI Bojonegoro, 2022)
Abstract: This qualitative descriptive study aims to determine and analyze students' mathematical reasoning abilities and self-concepts in terms of gender in seventh grade junior high school students based on triangles and quadrilaterals. The subjects of this study were students of class VII SMP, totaling 22 students. The research instrument was in the form of a test consisting of four description questions and 20 self-concept questions. The indicators of mathematical reasoning that are measured are drawing sketches, analogies, proportional reasoning, and generalizations. The results of this study showed that the mathematical reasoning abilities of female students performed better than male students. In addition, students' self-concept analysis based on questionnaire data on mathematical reasoning abilities was in the good category.Keywords: Mathematical Reasoning; Self Concept; Gender